The influence of high-level beliefs on self-regulatory engagement: evidence from thermal pain stimulation - Lynn, Margaret T.; Van Dessel, Pieter; Brass, Marcel (Frontiers in Psychology, 2013)
Determinist beliefs have been shown to impact basic motor preparation, prosocial behavior, performance monitoring, and voluntary inhibition, presumably by diminishing the recruitment of cognitive resources for self-regulation. We sought to support and extend previous findings by applying a belief manipulation to a novel inhibition paradigm that requires participants to either execute or suppress a prepotent withdrawal reaction from a strong aversive stimulus (thermal pain). Action and inhibition responses could be determined by either external signals or voluntary choices. Our results suggest that the reduction of free will beliefs corresponds with a reduction in effort investment that influences voluntary action selection and inhibition, most directly indicated by increased time required to initiate a withdrawal response internally (but not externally). It is likely that disbelief in free will encourages participants to be more passive, to exhibit a reduction in intentional engagement, and to be disinclined to adapt their behavior to contextual needs.